2011
DOI: 10.4314/cajeb.v6i2.68528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethanolic extract of Senecio biafrae on puberty onset and fertility in immature female rat.

Abstract: Senecio biafrae is a medicinal plant widely used by traditional healers in the western region of Cameroon for the treatment of woman infertility. In the course of the evaluation of its effect on puberty onset and some physiological parameters of fertility, different doses of its ethanolic extract were orally administered to immature female rats for 30 days. Body, ovarian, uterus weight; uterine, ovarian proteins or cholesterol level as well as data on puberty onset were recorded. A linear increase in the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
3
6
1
Order By: Relevance
“…The extraction yield showed a value of 27.06%, higher than other reports. In fact, it has been reported that the extraction yield of the aerial parts of other species of Senecio with 95% ethanol (yield of 5.60% in S. biafrae [ 26 ] and 12.57% in S. aegyptius [ 27 ], methanol (yield of 13.85% in S. gibbosus [ 28 ]) or water (yield of 13.60% in S. candicans [ 29 ]) was considerably lower than values obtained in this study.…”
Section: Resultscontrasting
confidence: 81%
“…The extraction yield showed a value of 27.06%, higher than other reports. In fact, it has been reported that the extraction yield of the aerial parts of other species of Senecio with 95% ethanol (yield of 5.60% in S. biafrae [ 26 ] and 12.57% in S. aegyptius [ 27 ], methanol (yield of 13.85% in S. gibbosus [ 28 ]) or water (yield of 13.60% in S. candicans [ 29 ]) was considerably lower than values obtained in this study.…”
Section: Resultscontrasting
confidence: 81%
“…Moreover, many clinical and pharmacological studies attest the efficiency of some of these plants in the treatment of female infertility. The estrogenic effect of Senecio biafrae and its inductive potential on the onset of puberty was demonstrated on immature female rats (Lienou et al, 2010). The FSH-like and anti-estrogenic effects of Eremomastax speciosa, its inductive effect on ovulation as well as its regularizing effect on the estrous cycle of female rats were proven (Lemfack, 2007;Ngoufack, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…For example, the association of Senecio biafrae, Eremomastax speciosa and Ageratum conyzoides as they claimed is employed in women with menstrual disorders. In the mixture, Solanecio biafrae and Eremomastax speciosa could specifically act on the normalization of the menstrual cycle through the induction of ovarian folliculogenesis (Ngoufack, 2009;Lienou et al, 2010) and the great anti-microbial action of Ageratum conyzoides could help to fight any infection of the reproductive system. It is through this procedure that they may sometimes defeat the ailment.…”
Section: Cissus Quadrangularismentioning
confidence: 99%
“…Senecio biafrae (Compositae) is known for its therapeutic virtues, notably in Nigeria where it is used in the treatment of diabetes mellitus (Adebayo, 2009). Senecio biafrae leaves, "Worowo" (Yoruba), are used by traditional practitioners to treat infertility in women (Lienou et al, 2010), heart problems (Ayodele, 2005), as well as serve as antihypertensive (Olowokudejo et al, 2008). Hypolipidaemic, hypoglycemic and antioxidants properties of Launaea taraxacifolia ̀ (Asteraceae) plant, Ẹfó ̣ yánrin (Yoruba), have also been reported (Dansi et al, 2008;Obi, 2011;Arawande et al, 2013).…”
Section: Introductionmentioning
confidence: 99%